Students' Speaking Ability Santo Arnoldus Janssen Secondarry Secondary High School Kupang through Public Speaking Training - Yoseph Riang; Donna Isra Silaban; Innosensia E Isavela Ndiki Satu; Sintia Bili (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In this modern era, every individual needs to continue develop themselves by increasing their abilities so that they can become quality individuals, be able to adapt and to compete with other people. One way to be done is by improving public speaking. This training aims to improve the public speaking skills of students at Santo Arnoldus Janssen Secondary High School Kupang. The trainer in this training uses a lecture method completed by slides presentation to provide materials related to the basics of public speaking. Besides, this activity is also conducted with skills training, initial tests, discussions and final tests on public speaking. The aim is that all training participants will not only understand all the theories they have learned, but can directly practice it. The results of the training showed that at the beginning of the training activities, the students at Santo Arnoldus Janssen Secondary High School Kupang on the average did not fully know the theory and practice related to the basics of public speaking. This can be seen when they are asked questions about the meaning of public speaking, history, scope, methods, benefits, objectives, functions, improving skills and the urgency in conveying messages in front of an audience. Generally they cannot answer these questions. Apart from that, the average of participants were not able to practice it. The evidence was when they carried out an initial simulation regarding how to do public speaking appropriately in front of an audience. After the discussion, it was indicated that in the second simulation or final test the participants did not only underst and , but also has the ability to practice public speaking before an audience.